(untitled) (The Pakistan Development Review, 2006)
Fiscal sustainability is required to attain and maintain the long-run steady-state growth in emerging markets, to create fiscal space for rural and urban poverty, to safeguard financial stability, and to achieve the overall Millennium Development Goals. This can be done by providing financial support and by encouraging further research in this area. This book analyses the issues in the context of international experience and its implications for Egypt. It touches on issues of fiscal deficit and public debt sustainability, debt management, efficiency and equity of social expenditure, and public investment, the will and power to achieve civil service reform, and transparency and equitability of the budgetary process. It fills a gap in research.